Convalescent Plasma Therapy: The Early Use in Moderate to Severe COVID-19 Patients in Hospitals with Limited Resources - Mahdi, Bagus Aulia; Suryantoro, Satriyo Dwi; Romadhon, Pradana Zaky; Windradi, Choirina; Widiyastuti, Krisnina Nurul; Novendrianto, Dwiki; Widiasi, Etha Dini; Agustin, Esthiningrum Dewi; Firdausa, Sarah; Alkaff, Firas Farisi (Indonesian Journal of Tropical and Infectious Disease, 2021)
COVID-19 cases in Indonesia in the period of June-July 2021 showed a catastrophic spike. During this period, a recently discovered variant, the delta variant, appeared to be one of the sources of COVID-19 infection. Treatment modalities are limited due to reduced stock of drugs. A case of a 63-year-old man has been reported, with a history of having been vaccinated with two doses of Sinovac, experiencing moderate-to-severe symptoms of COVID-19 infection then given convalescent plasma therapy since his initial admission to the hospital. Three days after being given convalescent plasma therapy, the improvement was noticeable. Shortness of breath, cough, fever, and weakness were less complained. On the seventh day the patient fully recovered and got discharged. Convalescent plasma therapy was e ective in early stage and was able to improve outcomes. Indonesia needs sucient stocks of convalescent plasma as a therapy to overcome the limitations of medicines.